(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The reasonability of using communicative approach in the process of teaching future aviation specialists to speak English has been proved in the given article. The definition of the term “communication” as a basic notion of communicative approach has been offered. Communication can be defined as exchange of thoughts and information. Formulated by E. Passov principles of communicative learning have been presented: the principle of speaking and mental activity, the principle of individualization, the principle of functionality, the situational principle and the principle of novelty. The conditions of effective application of communicative approach and tendencies relevant for teaching a foreign language have been defined. The tendencies are the following: communicative orientation of all kinds of learning; the main link in the teaching process is not a teacher but a student; making students interested in the learning process according to their interests, abilities and needs; teaching materials are presented according to situational and subject or functional principle; the main types of interaction are pair and group work; communicative approach in the process of learning a language has contributed into appearing of non-traditional attitude towards errors. One of the drawbacks of communicative approach is unsystematic presentation of grammar material. In the process of research it has been found out that success of implementation of communicative approach depends on a number of factors: the level of teacher’s professional training; knowledge of cadets’ individual peculiarities and abilities; usage of authentic teaching materials; formation of cadets’ communicative competency with the help of four kinds of activities, such as reading, writing, speaking and listening. The author of the article points out the term «approach» means the strategy of teaching. The fundamental principle of communicative approach is focusing on communicative competency as a basic one, spontaneity and natural character of communication process, considering students’ individual peculiarities, abilities, interests and future job possibilities. Having conducted the research we have come to the conclusion that communicative approach can be successfully implemented in the process of teaching future aviation specialists to speak English. Pair work is the most common type of activity as communication in real life takes place between a pilot and an air traffic controller. Group work is also very popular as it helps students to overcome language barrier and fear of speaking. The students are asked to agree or disagree with the given statements, to find solutions to different problem situations.